VIRTUAL LABORATORIES AND MOBILE LABORATORY STANDS AS EDUCATIONAL TECHNOLOGIES IN PHYSICS TEACHING - Abduvoxid A.Ganiev (PEDAGOGS, 2024)
Abstract: The article analyzes the use of educational technologies in teaching physics using virtual laboratories and mobile laboratory stands.